WOMEN EMPLOYMENT AND ENTREPRENEURSHIP: A SYSTEMATIC REVIEW OF TRENDS AND PATTERNS POST UTILIZATION OF NEW MEDIA TECHNOLOGIES - Gupta, Anurag; Butt, Aaqib Anwaar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The rapid spread of COVID-19 across the country and the subsequent lockdowns disrupted a substantial number of businesses across the country. Small businesses, especially those owned and operated by women, have been affected by the epidemic, which has exacerbated the situation. In addition, the information gleaned from the applications revealed that despite these challenging circumstances, women had demonstrated remarkably high levels of leadership, happiness, and resilience. In 2020, women initiated twice as many Facebook-based fundraising campaigns as men. Moreover, female-initiated events received twice as many donations, accounting for 64% of the total cash donations. In addition, this research provides information on how businesswomen can utilize social media successfully in their operations, as well as variables that are advantageous to these businesswomen when conducting online business on social media. The objective of this study is to examine the pattern and trend of women's employment and entrepreneurship post utilization of new media. The study reveals that despite the presence of educational and socioeconomic issues, tribal women entrepreneurs have emerged in the last few decades with the aid of government-sponsored economic programs, and they are also improving their society.